Leonid Tyulpa. The architect of the soviet period of mass industrial development - Bouryak, Alexander; Lavrentiev, Igor; Antonenko, Nadiia (ZARCH, 2017)
The design approach employed by Kharkiv-based architect Leonid Tyulpa evolved from the early 1950s to the late 1970s. The architect’s career reflected the state of the whole Soviet architectural design in the second half of the XX century. His creative work encompassed all the milestones of housing development practice in the country. L.Tyulpa’s career started in 1951-1956 with restoration design projects in cities damaged during WW II. The years between 1956 and 1958 marked a transitional stage when the architect broke with old design traditions. In the third stage of his career, L.Tyulpa embarked on developing a new practice of designing prefabricated housing, searching for economical and feasible design solutions (1958-1963), with Pavlovo Pole housing estate being a vivid example of this period. Starting from 1963 the principles of creating the so-called “micro-districts” were implemented into the old city tissue, leading to a comprehensive reconsideration of the city and its role. The final stage of his career saw the appearance of a totally new vast housing area in Kharkiv. It was Saltovskiy housing estate for 300,000 dwellers, which became the utmost manifestation of the modernist way of thinking.KEYWORDS: Mass housing; postwar, micro-district; Soviet modernism; Tyulpa; Saltovskiy housing estate; Pavlovo Pole; Ukraine.